Bis (benzimidazol-2-yl) disulphide: An efficient water soluble inhibitor for corrosion of mild steel in acid media - Ahamad I.; Quraishi M.A. (My University, 2025)
The inhibition effect of Bis (benzimidazol-2-yl) disulphide (BIMDS) on corrosion behavior of mild steel (MS) in 1.0 M HCl and 0.5 M H2SO4 was studied using different techniques. These studies have shown that studied compound is a good inhibitor for MS in 1.0 M HCl and 0.5 M H2SO4 solutions. Inhibitor showed better performance in 0.5 M H2SO4 solutions than 1.0 M HCl. Polarization measurements indicated that BIMDS is a mixed-type inhibitor in both acid media. Adsorption of inhibitor molecules on the mild steel surface showed Langmuir isotherm model in both acid media. © 2009 Elsevier Ltd. All rights reserved.